2021
DOI: 10.7717/peerj.10862
|View full text |Cite
|
Sign up to set email alerts
|

Detection and monitoring of insect traces in bioaerosols

Abstract: Studies on bioaerosols have primarily focused on their chemical and biological compositions and their impact on public health and the ecosystem. However, most bioaerosol studies have only focused on viruses, bacteria, fungi, and pollen. To assess the diversity and composition of airborne insect material in particulate matter (PM) for the first time, we attempted to detect DNA traces of insect origin in dust samples collected over a two-year period. These samples were systematically collected at one-month inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Considering all arthropod groups though, a substantial diversity of species was detected (91 unique arthropod species could be identified to species level), showcasing that eDNA from insects and other arthropods is present in the air and can be targeted for species detection and monitoring. This corroborates the results from Pumkaeo et al (2021) who report the detection of 55 species in 16 orders belonging to the phylum Arthropoda. Moreover, the unspecific amplification of the COI primers showed that eDNA from a wide variety of taxa is present in the air, including vertebrates, mollusks, annelids, plants, green algae, oomycetes, and many species of fungi—both ascomycetes and basidiomycetes (the former representing many filamentous and single‐celled species while the latter includes most species commonly known as ‘mushrooms’ that produce airborne spores).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Considering all arthropod groups though, a substantial diversity of species was detected (91 unique arthropod species could be identified to species level), showcasing that eDNA from insects and other arthropods is present in the air and can be targeted for species detection and monitoring. This corroborates the results from Pumkaeo et al (2021) who report the detection of 55 species in 16 orders belonging to the phylum Arthropoda. Moreover, the unspecific amplification of the COI primers showed that eDNA from a wide variety of taxa is present in the air, including vertebrates, mollusks, annelids, plants, green algae, oomycetes, and many species of fungi—both ascomycetes and basidiomycetes (the former representing many filamentous and single‐celled species while the latter includes most species commonly known as ‘mushrooms’ that produce airborne spores).…”
Section: Discussionsupporting
confidence: 92%
“…For insects, Pumkaeo et al (2021) collected air samples with an Andersen AN‐200 sampler with a flow rate of 20 l/min. As the samples were collected monthly, a single sample represented an approximate volume of 835 m 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It further emphasises the need for incorporation of field replicates, as is recommended for other eDNA substrate types 36 . Studies of airborne eDNA monitoring of insects have not incorporated and contrasted field replicates 37,38 , however in studies on marine eDNA, a similar patchy distribution of DNA has been observed with paired field replicates not detecting the exact same community 39,40 . In the present study, we found no differences in the vertebrate composition between microhabitats, nor sampling sites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as with any novel method, optimisations are needed to further strengthen the use of airborne eDNA for vertebrate monitoring. The study adds terrestrial vertebrates to the recent work demonstrating that plants 49 and insects 37,38 can be detected in natural systems using airborne eDNA. Thereby, airborne eDNA coupled with DNA metabarcoding can become a key tool to complement existing methods to achieve comprehensive biodiversity assessments, something which is in great demand 50 .…”
Section: Discussionmentioning
confidence: 99%